Chaihu Longgu Muli Decoction for post-stroke insomnia: A protocol for systematic review and meta-analysis. Issue 15 (14th April 2023) - Huang, Xuedi; Xiong, Yue; Jiang, Sichen; Tang, Lihua; Lin, Xingzhen; Fang, Xinyue; Shi, Yuzhen; Lan, Wanning; Xie, Yaying; Peng, Tianzhong
Abstract : Background: Poststroke insomnia (PSI) is a frequent complication of stroke usually as a comorbidity of poststroke depression and mainly occurs within the first 6 months after stroke. [1 ] Addressing PSI to improve stroke prognosis is of great value. Herbal medicine like Chaihu Longgu Muli Decoction (CLMD), which is commonly considered to be a good treatment for depression and epilepsy, has the therapeutic potential on PSI; however, insufficient systematic reviews were conducted to testify its efficacy. Therefore, the objective of this paper is to provide reliable evidence of the efficacy and safety of CLMD on PSI and a foundation for further investigation. Methods: The literature of clinical randomized controlled trials (RCTs) regarding CLMD for PSI published before June of 2021 will be retrieved in the databases, and 2 investigators will be asked to collect and crosscheck the data independently. For the including studies, the quality evaluation on methodology will be assessed in the light of the Cochrane Handbook for Systematic Review of Interventions V.5.1.0 as well as the quality of evidence will be evaluated by the Grading of Recommendations Assessment, Development, and Evaluation. Besides, the assessment of heterogeneity and reporting bias, the sensitivity analysis and the subgroup analysis will be conducted. Stata 15 will be applied to analyze the above data. Results: The review will conduct a high-quality synthesis on present evidence of CLMD for PSI. Conclusion: The conclusion of the study will indicate whether CLMD is effective and safe for PSI.